Functional Molecular Silicon Compounds II Low Oxidation States - Scheschkewitz, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Carsten Präsang and David Scheschkewitz Silyl Anions Masafumi Unno Substituted Polyhedral Silicon and Germanium Clusters Burgert Blom and Matthias Driess Recent Advances in Silylene Chemistry: Small Molecule Activation En-Route Towards Metal-Free Catalysis Takeaki Iwamoto and Shintaro Ishida Multiple Bonds with Silicon: Recent Advances in Synthesis, Structure, and Functions of Stable Disilenes Eric Rivard Recent Advances in the N-Heterocyclic Carbene-Supported Chemistry of Silicon.
Silyl Anions -- Molecular Silicon Clusters -- Silylenes -- Multiple bonds with Silicon -- NHC-stabilized low valent silicon compounds.
Keywords: Inorganic chemistry; Organic chemistry; Pharmaceutical technology; Inorganic Chemistry; Organic Chemistry; Pharmaceutical Sciences/Technology.